Kinematic modelling and simulation of PID controlled SCARA robot with multiple tool end effector. (23rd February 2021) - Mohan, M. Saravana; Anbumalar, V.; Kumaran, S. Thirumalai
At present, a mechatronics approach is adopted to develop and control an electromechanical system like robots. In this paper, the three-dimensional (3D) computer aided drawing (CAD) model of selective compliant assembly robot arm (SCARA) with a multiple tool end effector (MTEE) was developed using SolidWorks software and the novel attempt of PID controller-based simulation was carried out in SimMechanics simulation environment of MATLAB software is presented. By linking CAD Modelling SolidWorks and MATLAB/SimMechanics software, the 3D CAD model of the SCARA is transformed into series of blocks representing the multibody electromechanical system. The motion sensing capability and the simulation modes of SimMechanics incorporated with PID controller are applied for the position control of robotic manipulator joints to make the end effector to reach the target position accurately. The results of the SimMechanics simulation presented in this paper infer the suitable parameters to position of the manipulator can be controlled precisely.